2020
DOI: 10.1016/j.ebiom.2020.102895
|View full text |Cite
|
Sign up to set email alerts
|

A surrogate of Roux-en-Y gastric bypass (the enterogastro anastomosis surgery) regulates multiple beta-cell pathways during resolution of diabetes in ob/ob mice

Abstract: Background Bariatric surgery is an effective treatment for type 2 diabetes. Early post-surgical enhancement of insulin secretion is key for diabetes remission. The full complement of mechanisms responsible for improved pancreatic beta cell functionality after bariatric surgery is still unclear. Our aim was to identify pathways, evident in the islet transcriptome, that characterize the adaptive response to bariatric surgery independently of body weight changes. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 104 publications
(192 reference statements)
0
7
0
Order By: Relevance
“…Our data with this approach did not, however, provide compelling evidence for such changes after surgery, though our sample size was relatively small. It is conceivable, therefore, that changes in the expression of genes more directly associated with the control of Ca 2+ dynamics and connectivity in and between β-cells, including Trpm2 and Gjd2 (Cx36) 69 and others associated with insulin secretion 44 , play a role in the improvements observed postsurgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data with this approach did not, however, provide compelling evidence for such changes after surgery, though our sample size was relatively small. It is conceivable, therefore, that changes in the expression of genes more directly associated with the control of Ca 2+ dynamics and connectivity in and between β-cells, including Trpm2 and Gjd2 (Cx36) 69 and others associated with insulin secretion 44 , play a role in the improvements observed postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in metabolic signalling by glucose, particularly changes in the glycolytic and oxidative metabolism of the sugar by mitochondria, are observed in islets from human subjects with T2D 68 and are implicated in the recovery of glucose tolerance after Roux-en-Y-like gastric surgery in the mouse 69 . In the former case, this is likely to involve decreases in the expression of the critical β-cell glucose transporter, GLUT2/SLC2A2, and in the low affinity glucose phosphorylating enzyme glucokinase (GCK) 70 .…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant (500 µL) was immediately collected and stored at −20 °C until being assayed for insulin by ELISA (ultra-sensitive mouse insulin ELISA Kit; Crystal Chem, #90080, the Netherland). The islets were homogenized in protein extraction buffer and stored until insulin content determination by ELISA (ultra-sensitive mouse insulin ELISA Kit; Crystal Chem, #90080, Netherland), as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate if the altered sweet taste transduction pathway gene expression within EECs could be corrected after weight loss and diabetes remission, we used EGA surgery in mice (a surrogate of the RYGB in humans), as described before (20,28). EGA surgery forms a loop that excludes the duodenum and proximal jejunum from alimentary tract.…”
Section: The A-gustducin Gene Expression Is Partly Rescued By Surgery-induced Hyperglycemia Remission In Micementioning
confidence: 99%
“…The rise of postprandial GLP-1 secretion after Roux-en-Y gastric bypass (RYGB) may contribute to this improvement (15)(16)(17)(18)(19). After RYGB, the rapid delivery of undigested nutrients to the lower small intestine may affect the regulation of taste receptors and/or glucose transporters on EECs, resulting in an enhanced release of GLP-1 (20)(21)(22) although a recent study demonstrated that lengthening of the intestinal bypass in RYGB does not affect GLP-1 secretion (23). Therefore, the mechanisms driving the alteration of enterohormone secretion in obesity and after RYGB might not be restricted to GLP-1 incretin effects alone (17).…”
Section: Introductionmentioning
confidence: 99%